New Entodiniomorphid Ciliates, Buetschlia minuta n. sp., B. cirrata n. sp., Charonina elephanti n. sp., from Asian Elephants of Turkey - GÜrellİ, GÖzde (Magnolia Press, 2019)
Three new entodiniomorphid species, Buetschlia minuta n. sp., Buetschlia cirrata n. sp., and Charonina elephanti n. sp., were described from the hindgut of Asian elephants (Elephas maximus) from Gaziantep, Turkey. B. minuta n. sp. has an ovoid body shape with a truncated anterior end and a rounded posterior end, an adoral ciliary zone surrounding the cytostome, somatic ciliary rows in the anterior two thirds of the body, an ovoid macronucleus without a constant position, and a concretion vacuole in the anterior one third of the body. B. cirrata n. sp. has an ovoid body shape with the anterior end truncated and the posterior end rounded, an adoral ciliary zone surrounding the cytostome, unevenly distributed somatic cilia, an ovoid macronucleus without a constant position, and a concretion vacuole in the anterior one third of the body. C. elephanti n. sp. has an ovoid body shape with both ends rounded, an ovoid macronucleus without a constant position, two buccal ciliary zones, an adoral ciliary zone, a vestibular ciliary zone, three somatic ciliary zones, a dorsal ciliary zone, two posterior ciliary zones, dorsal and ventral, and a vestibulum with a Y-shaped infraciliature.
Keywords: Mouth; Turkey; Elephants; Octopodiformes; Animals; Ciliophora